Village Women's Politics: Maloe Mamat and Ume Hana as Village Heads' Victory Strategy - Barros Mbiri, Adeodata Laniria Charla; Bria, Fridus; Barros Mbiri , Adeo Dato Januario (Trigin Publisher, 2024)
This research expands the study of women's political strategies in local democracy which is the focus of research in Letneo Village, TTU Regency. This research uses Peter Schoder's theory of political strategy as a knife in analyzing the social facts that occur. The method used is descriptive qualitative with the technique for determining informants being purposive sampling and data collection techniques in the form of documentation, interviews and observation and data triangulation. The results found in achieving victory Mariana Tahu used the maloe mamat and ume hana strategies as defensive and offensive strategies. This research also expands studies on political strategy theory that strategies using local culture are still relevant in Indonesia amidst the rise of strategies using social media and money politics, especially in villages that still adhere to local culture. A strategy that is quite relevant to apply in areas where patriarchal culture is very strong is to use local culture which is adopted with a very subtle approach so as to get support from men. Based on this research, there are suggestions for women to instill a courageous and ethical mentality to fight in the election space so that they can become a channel for aspirations that represent women's interests.